KETERSEDIAAN PANGAN SEBAGAI INDIKATOR PETA KETAHANAN DAN KERENTANAN PANGAN - Kurniawan, Dodik Tri (Universitas Nahdlatul Ulama Sidoarjo, 2015)
The availability of food is determined by food production in the region, food trade through market mechanisms in the region, stocks held by traders and government reserves, and food aid from the government or other organizations. Methods of identifying areas vulnerable to food at the district level is done by using a variety of indicators used in the analysis of food insecurity by adjusting the indicator FSVA (food security and vulnerability atlas) used in the analysis of food insecurity nationwide. The ratio of consumption in Sumenep shows that the ratio of normative consumption in each district enough variation, in which almost all the districts identified villages are high surpluses and high deficits. Village high surplus amounted to 114 region. The results of analysis of vulnerability to food security in Sumenep, the village obtained the following conclusions based on the level of vulnerability to food security in Sumenep generally included in the priority 6 the number of 216 region, or 65.06% of the total number of region. Keywords: region, insecurity, food, mapping.